Inventory and ecology of avifauna in Universitas Andalas campus complex, Indonesia - Dewangga, Adib S.; Janra, Muhammad N. (Syiah Kuala University, 2024)
Universitas Andalas campus is located at Payakumbuh region, West Sumatra, Indonesia. This campus is surroundedby forest and settlement. This study aimed to determine species inventory and its ecological condition in Andalas University campus complex (UACC), Limau Manis, Padang, West Sumatra. It had been conducted between October 2022 and January 2023, where the survey was carried out at three zonation in UACC based on its level of anthropogenic interference; campus entrance with the heaviest disruption (campus boulevard), main campus, and forest-edge that bordered with the eastern side of campus. Point count method was applied along ten observing points which approximately 100 m distance from one to another; the forest-edge were surveyed with only five points. Species and individual numbers were recorded within maximum 100 m radius from center of each point for ten minutes. The data was then analyzed for its diversity, similarity across sites and typical species per survey site. The study recorded 38 bird species with total 418 individuals; they belong to 20 families and 7 orders. The overall bird diversity in UACC was moderate (H = 2.9), with the lowest was observed at the campus boulevard (H = 2.1) followed by forest-edge (H = 2.2) and the highest was at lecturing complex (H = 2.6). The similarity among sites was low to moderate (21.7% J 52%) which suggested some species are typical to their respective habitat site. The forest-edge site has the most typical species (n = 14) among other habitats.This study also hinted the possibility of the occurrence of mixed-flock bird species event at the main campus habitat between yellow-vented bulbul Pycnonotus goiavier and Coppersmith barbet Psilopogon haemacephala along with some other participants.